The impact of network convergence on telecommunications software. - Moyer, S. (IEEE Communications magazine)
This describes a converged network architecture and then discusses why it needs to be open and programmable and how this can be accomplished. A discussion of two approaches to open/programmable networks-JAIN and Parlay-is provided to highlight the key ideas. The converged network is a key player in e-business and the next-generation applications currently being developed for the growing digital economy. We discuss the role of telecommunications bandwidth trading and application integration in next-generation applications (NGAs) and their relevance to converged networks. Some of the challenges software engineers and programmers can expect to encounter while trying to build these networks are also discussed